Virtual MOA signing between De La Salle University and De La Salle Araneta University on the accreditation of the BS animal biology program - College of Science - De La Salle University, Manila (Animo Repository, 2021)
The College of Science De La Salle University in partnership with the College of Veterinary Medicine and Agricultural Sciences De La Salle Araneta University cordially invited the academic community to the Virtual MOA Signing between De La Salle University and De La Salle Araneta University on the Accreditation of the BS Animal Biology Program